Characterization of a Novel Human Herpesvirus 8-Encoded Protein, vIRF-3, That Shows Homology to Viral and Cellular Interferon Regulatory Factors - Lubyova, Barbora (American Society for Microbiology, 2000)
The genome of the human herpesvirus 8 (HHV-8) contains a cluster of open reading frames (ORFs) encoding proteins with homology to the cellular transcription factors of the interferon regulatory factor (IRF) family. Two of these homologues, vIRF-1 and vIRF-2, were previously identified and functionally analyzed. In this study, we have characterized a novel gene, designated vIRF-3, encoded within the previously predicted ORF K10.5 and our newly identified ORF K10.6. Northern blotting of RNA extracted from BCBL-1 cells with a vIRF-3-specific probe and reverse transcription-PCR analyses revealed a single transcript of 2.2 kb with a splice present in the coding region. The vIRF-3 mRNA levels in BCBL-1 cells were increased upon 12-O-tetradecanoylphorbol-13-acetate treatment, with kinetics of expression similar to those of the early immediate genes. The vIRF-3 ORF encodes a 73-kDa protein with homology to cellular IRF-4 and HHV-8-encoded vIRF-2 and K11. In transient transfection assays with the IFNACAT reporter, vIRF-3 functioned as a dominant-negative mutant of both IRF-3 and IRF-7 and inhibited virus-mediated transcriptional activity of the IFNA promoter. Similarly, the overexpression of vIRF-3 in mouse L929 cells resulted in inhibition of virus-mediated synthesis of biologically active interferons. These results suggest that by targeting IRF-3 and IRF-7, which play a critical role in the activation of alpha/beta interferon (IFN) genes, HHV-8 has evolved a mechanism by which it directly subverts the functions of IRFs and down-regulates the induction of the IFN genes that are important components of the innate immunity.